Advances in understanding the pathogenesis of red cell membrane disorders. (31st July 2019) - Iolascon, Achille; Andolfo, Immacolata; Russo, Roberta
Summary: Hereditary erythrocyte membrane disorders are caused by mutations in genes encoding various transmembrane or cytoskeletal proteins of red blood cells. The main consequences of these genetic alterations are decreased cell deformability and shortened erythrocyte survival. Red blood cell membrane defects encompass a heterogeneous group of haemolytic anaemias caused by either (i) altered membrane structural organisation (hereditary spherocytosis, hereditary elliptocytosis, hereditary pyropoikilocytosis and Southeast Asian ovalocytosis) or (ii) altered membrane transport function (overhydrated hereditary stomatocytosis, dehydrated hereditary stomatocytosis or xerocytosis, familial pseudohyperkalaemia and cryohydrocytosis). Herein we provide a comprehensive review of the recent literature on the molecular genetics of erythrocyte membrane defects and their reported clinical consequences. We also describe the effect of low‐expression genetic variants on the high inter‐ and intra‐familial phenotype variability of erythrocyte structural defects.